2020
DOI: 10.33776/erebea.v10i0.4959
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behaviors among Young People: The Role of Developmental Assets

Abstract: Fecha de recepción: 24 de septiembre de 2020 Fecha de aceptación: 26 de octubre de 2020 Palabras ClaveDesarrollo positivo juvenil; activos de desarrollo; conductas de riesgo; Noruega.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…Finally, betting in the last year was related to lower scores for commitment to learning, social skills, positive values, boundaries and expectations, and social support. These results are in harmony with previous studies, such as those by and in the USA and Sahar et al (2020) in Norway. Thus, as indicated by Oliva (2015), developmental assets constitute the basis for young people's healthy development.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, betting in the last year was related to lower scores for commitment to learning, social skills, positive values, boundaries and expectations, and social support. These results are in harmony with previous studies, such as those by and in the USA and Sahar et al (2020) in Norway. Thus, as indicated by Oliva (2015), developmental assets constitute the basis for young people's healthy development.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, betting in the last year was related to lower scores for commitment to learning, social skills, positive values, boundaries and expectations, and social support. These results are in harmony with previous studies, such as those by Leffert et al (1998) and Atkins et al (2002) in the USA and Sahar et al (2020) in Norway. Thus, as indicated by Oliva (2015), developmental assets constitute the basis for young people's healthy development.…”
Section: Discussionsupporting
confidence: 92%
“…Less empowerment and less constructive use of time were also predictors of social victimisation. In Norway, Sahar et al (2020) concluded that two internal assets (i.e., positive values and social competence) and two external assets (i.e., support and boundaries and expectations) predicted a risk behaviour (e.g. drunkenness, violence and delinquency) in young people.…”
mentioning
confidence: 99%
“…During this life stage, the search for self-identity becomes more intense [2]. Therefore, in this search, adolescents may present maladaptive behaviors such as poor school performance, drug use and intergenerational conflicts [3,4]. Adolescence lasts approximately from 10 to 19 years old, although many authors agree that several current factors such as delayed parenthood, more time in education, as well as less job stability have caused it to be extended to 29 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Other important authors like Freud and neo-Freudian authors such as Erik Erikson increased this initial negative vision of adolescence by arguing that this stage was marked by problems that needed to be corrected [10,11]. In other words, these and other authors characterized adolescents based on deficit models by labeling them as problematic, passive beings, ignoring all the potential they may have [4,12,13].…”
Section: Introductionmentioning
confidence: 99%